Bilateral Improvements in Lower Extremity Function After Unilateral Balance Training in Individuals With Chronic Ankle Instability - Hale, Sheri A. (National Athletic Trainers Association, 2014)
CONTEXT: Bilateral improvements in postural control have been reported among individuals with acute lateral ankle sprains and individuals with chronic ankle instability (CAI) when only the unstable ankle is rehabilitated. We do not know if training the stable ankle will improve function on the unstable side. OBJECTIVE: To explore the effects of a unilateral balance-training program on bilateral lower extremity balance and function in individuals with CAI when only the stable limb is trained. DESIGN: Cohort study. SETTING: University clinical research laboratory. PATIENTS OR OTHER PARTICIPANTS: A total of 34 volunteers (8 men, 26 women; age = 24.32 ± 4.95 years, height = 167.01 ± 9.45 cm, mass = 77.54 ± 23.76 kg) with CAI were assigned to the rehabilitation (n = 17) or control (n = 17) group. Of those, 27 (13 rehabilitation group, 14 control group) completed the study. INTERVENTION(S): Balance training twice weekly for 4 weeks. MAIN OUTCOME MEASURE(S): Foot and Ankle Disability Index (FADI), FADI Sport (FADI-S), Star Excursion Balance Test, and Balance Error Scoring System. RESULTS: The rehabilitation and control groups differed in changes in FADI-S and Star Excursion Balance Test scores over time. Only the rehabilitation group improved in the FADI-S and in the posteromedial and anterior reaches of the Star Excursion Balance Test. Both groups demonstrated improvements in posterolateral reach; however, the rehabilitation group demonstrated greater improvement than the control group. When the groups were combined, participants reported improvements in FADI and FADI-S scores for the unstable ankle but not the stable ankle. CONCLUSIONS: Our data suggest training the stable ankle may result in improvements in balance and lower extremity function in the unstable ankle. This further supports the existence of a centrally mediated mechanism in the development of postural-control deficits after injury, as well as improved postural control after rehabilitation.